2011
DOI: 10.1111/j.2042-3306.2010.00138.x
|View full text |Cite
|
Sign up to set email alerts
|

An anatomical study to evaluate the risk of pulpar exposure during mechanical widening of equine cheek teeth diastemata and ‘bit seating’

Abstract: SummaryReasons for performing study: Cheek teeth (CT) diastemata are a major equine dental disorder that can be treated by mechanically widening the diastemata. There is limited anatomical knowledge of the spatial relationships of the individual pulps to the adjacent interproximal surfaces; on the risks of exposing the 6th pulp horn when performing the clinically unproven 'bit seating' procedure on Triadan 06s. Objectives: To describe the anatomical relationships between the occlusal and interproximal surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 15 publications
4
24
0
1
Order By: Relevance
“…The distance of the vital pulp to the mesial (rostral) and the distal (caudal) border of the cheek teeth varies between <3 mm and 9 mm (Kopke and Staszyk ; Bettiol and Dixon ; Dixon et al . ), with a mean distance of approximately 5–6 mm.…”
Section: Endodontic Cavities – Pulp Horns Common Pulp Chamber and Romentioning
confidence: 99%
“…The distance of the vital pulp to the mesial (rostral) and the distal (caudal) border of the cheek teeth varies between <3 mm and 9 mm (Kopke and Staszyk ; Bettiol and Dixon ; Dixon et al . ), with a mean distance of approximately 5–6 mm.…”
Section: Endodontic Cavities – Pulp Horns Common Pulp Chamber and Romentioning
confidence: 99%
“…Rasping periods of >30 s are more applicable for reduction of more significant focal dental overgrowths, where multiple pulp horns are likely to be susceptible to thermal damage. Recent studies have shown that subocclusal secondary dentine thickness in overgrown teeth can be as low and as variable as normal values . Marshall et al .…”
Section: Discussionmentioning
confidence: 99%
“…The burr is then placed vertically into the diastema and moved across the interdental space. As the distal pulp horns of cheek teeth lie very close to the caudal aspect of the teeth, an attempt must be made to remove most of the dental tissue from the rostral aspect of the tooth lying caudal to the diastema (Bettiol and Dixon ; Dixon et al . ).…”
Section: Treatmentmentioning
confidence: 99%